Occupational Exposure to Hot Environments: Florida Workers Need Help - Margaret Wan (University of North Florida, 2004)
This article draws the attention of the Florida community - employees, employers, public health practitioners, and policy-makers - to an occupational hazard particularly relevant to Florida, namely, exposure to hot environments in the workplace. Heat stress disorders adversely affect worker safety and productivity. In extreme cases, they may endanger the life of a worker. The Occupational Safety and Health Administration (OSHA) has not set a standard for heat stress requiring employers to control exposure. More than 30 years after the recommendations of the Standards Advisory Committee on Heat Stress, the time for such a standard is overdue.